The Effect of Computational-Based Learning Media Using the STAD Type Cooperative Model on Student Learning Outcomes and Motivation on the Subject of Intermolecular Forces - Nababan, Tiur Maida Br.; Pratiwi, Ledy; Nugraha, Asep Wahyu (International Journal of Research in STEM Education, 2023)
This study aims to determine the effect of computational chemistry-based learning media using the STAD type cooperative learning model on student learning outcomes and motivation on the subject of forces between molecules. The population in this study were grade X students in high schools in Medan city which amounted to 7 classes. The samples of this study were students of class X IPA 3 and X IPA 5, each of which amounted to 36 students. The research instruments used were test instruments in the form of 20 multiple choice questions and non-test in the form of 30 statements. The quality of the research instrument was tested using validity, reliability, difficulty level of questions and differentiating power to determine the questions that would be used as instruments in the study. The data analysis technique shows that in the learning outcomes hypothesis test, the t-count> t-table value is 5.03>1.666 and the results of the learning motivation hypothesis test, the t-count> t-table value is 3.12>1.666. This data shows that there is an effect of computational chemistry-based learning media using the STAD type cooperative learning model on student learning outcomes and motivation on the subject of forces between molecules.